Analisis Desain Citra pada Produk Kemasan Indomie dengan Metode Semiotika - Ahmad Riyadi Swandhani; Adek Cerah Kurnia Azis; Chris Chalik (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
In interacting socially, without realizing it, humans give an image to each other or to objects, due to the presence of objective (Visual) in this case the eye sees the object in the form of an appearance (Body), and the process is called an image because it gives perception, then gives different meanings according to their knowledge, the purpose of this research is to find out the design strategy for Indomie packaging, Indomie packaging also represents the meaning of the image of a product, this method uses a semiotic analysis method, namely an approach that tries to find the hidden meaning behind a sign, be it an image or text, so that in this writing, we get the results of Design as an image, in this case a product has its own concept or view/specialties that you want to show to other people, by making a design in the form of an advertisement, product or writing, then the design builds or represents the features that you want to display (image) so that people tend to like or enter the space of perfection built by the design, in fact they prioritize the image over its own function. The results of research on Indomie packaging are a series of illusions that are injected into a commodity, in order to control consumers, this eye illusion makes the packaging look like an anesthetic injection, so that consumers feel influenced by buying a noodle product, because the packaging displayed depicts an illusion that makes buyers feel When you buy this product, you will get what it looks like on the packaging, even though in reality it isn't.